Aspectos da inovação e o direito do trabalho - Cella, Silvana Machado (2012)
This study aims to analyze and discuss issues brought by the wave of innovation, particularly for research and development, relationships and rules on new partnerships, processes and products and aspects of the Labor Law. Starting from the assumption that innovation and labor law are institutions that have points of contact, a dialogue between these areas was accomplished, reflecting the needs to adopt changes in the institutes, framing of concepts and norms. As a premise, it is stated that the Labor Law came to correct inequalities and has been elaborated based on the principle of protection and, as a focus, a typical ratio of work, where the employer stands as a large industrial complex, which holds of technical and financial power, and the worker is shown as a person devoid of technical skill and total economic dependence, which has employment, lasting and stable, their only source of survival. This scenario, however, has been gradually changed in the era of innovation and informational paradigm to reveal a society based on connections and accelerated, in which there is great model of business , operating simultaneously in many countries, workers technically prepared, seeking autonomy and freedom to develop their ideas, and the establishment of business relationships that involve workers and companies, forming bonds creative and unusual. These factors cannot be ignored by the Labor Law. We addressed some of the relationships established in the Innovation Law such as partnerships between Scientific and Technological Institutions and private companies, the links between these and individuals, as creators and inventors, as well as the relationships that are formed in the process of incubation companies. Were also presented reflections on relationships derived from the innovation, such as the hiring of scholars and entities executing projects and crowdsourcing system. Taking also premised on the argument to the effect that articles 218 and 219 of the Constitution make room for the establishment of a special working links indicated above were analyzed in the light of the essential ideas of the Labor Law, culminating in proposals for the formulation of a new design and regulation of labor relations arising from the innovation